2004
DOI: 10.1167/iovs.02-1233
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Manipulation of Primate Retinas, II: Effects of Age, n–3 Fatty Acids, Lutein, and Zeaxanthin on Retinal Pigment Epithelium

Abstract: RPE cells are sensitive to the absence of macular pigment. Supplemental xanthophylls interact with n-3 fatty acid levels to produce asymmetries in the RPE profile. Xanthophylls and n-3 fatty acids are essential for the development and/or maintenance of a normal distribution of RPE cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 38 publications
2
56
0
3
Order By: Relevance
“…[20][21][22][23][33][34][35][36][37][38][39][40] Further, and notwithstanding the fact that many of these cross-sectional studies were performed in the pre-AREDS 2 era, it should be appreciated that lutein-containing supplements were commercially available since 1999, 41 and since that date their use grew substantially as a result of widespread dissemination of their putative benefits. [42][43][44][45][46][47][48] Meaningful comment on any such relationship should be predicated, therefore, on population-based studies where data were recorded pre-1999 and to subsequent population-based studies where the use of carotenoid-containing supplements was recorded and appropriately factored into analyses. Three [20][21][22] of four [20][21][22]35 (75%) population-based studies using data recorded pre-1999 found an inverse relationship between AMD and serum concentrations of L and/or Z, and this compares with none of one 38 (0%) population-based studies utilizing data recorded after 1999 where supplement use was recorded and factored into analyses (see Table 2).…”
mentioning
confidence: 99%
“…[20][21][22][23][33][34][35][36][37][38][39][40] Further, and notwithstanding the fact that many of these cross-sectional studies were performed in the pre-AREDS 2 era, it should be appreciated that lutein-containing supplements were commercially available since 1999, 41 and since that date their use grew substantially as a result of widespread dissemination of their putative benefits. [42][43][44][45][46][47][48] Meaningful comment on any such relationship should be predicated, therefore, on population-based studies where data were recorded pre-1999 and to subsequent population-based studies where the use of carotenoid-containing supplements was recorded and appropriately factored into analyses. Three [20][21][22] of four [20][21][22]35 (75%) population-based studies using data recorded pre-1999 found an inverse relationship between AMD and serum concentrations of L and/or Z, and this compares with none of one 38 (0%) population-based studies utilizing data recorded after 1999 where supplement use was recorded and factored into analyses (see Table 2).…”
mentioning
confidence: 99%
“…Leung et al measured the RPE cell density in normal Rhesus monkeys and found that it peaks at the center of the fovea and declines gradually with increasing eccentricity. 54 They examined the effects of age on the RPE cell density in a group of Rhesus monkeys, and found an increase in the RPE cell density with age. They also examined the effects of dietary supplementation with lutein or zeaxanthin on the RPE cell density in this group of monkeys.…”
Section: The Putative Protective Effect Of Macularmentioning
confidence: 99%
“…60 Using the same group of xanthophyll-free animals, Leung et al investigated the effect of age and dietary manipulation on the cell density of the RPE. 54 These Rhesus monkeys were supplemented with pure lutein or zeaxanthin, but were fed a diet with either low or adequate amounts of n-3 fatty acids. After a prolonged period of such supplementation (between 6 and 24 months), a change in the peak symmetry of RPE cell density was observed.…”
Section: Effect Of Lutein and Zeaxanthin Supplementation On The Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…6 MP is very likely to play an important role also in early phases of foveal development, in the enhancement of infant visual acuity, and in the protection against light-induced oxidative damage, 7 and it may be essential also for the development and/or maintenance of a normal distribution of RPE cells. 8 Furthermore, the development of AMD in the elderly is potentially linked to phototoxic light exposure and oxidative stress accumulated over the lifetime, including the childhood years, 9 in which oxidation-induced, potentially harmful, photosensitive compounds such as lipofuscin can already be generated in high concentrations. 10 Without knowledge of normal MP levels and their spatial distributions in infants and children, further progress on their potentially beneficial roles cannot proceed.…”
Section: Introductionmentioning
confidence: 99%